1997
DOI: 10.1016/s0029-7844(97)00247-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of penicillin G benzathine in pregnant group B streptococcus carriers

Abstract: In pregnant women, penicillin G benzathine levels are high enough to inhibit the growth of group B streptococcus for more than 4 weeks after injection with 4.8 million units. Further studies are needed to evaluate whether this regimen can prevent neonatal colonization and invasive group B streptococcus disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…Another study measured maternal and fetal penicillin G levels after one intramuscular dose of penicillin G benzathine. This study showed levels above the MIC at 30 days after injection 16. Our current investigation documents penicillin G levels in the fetus using the current intravascular CDC dosing regimen.…”
Section: Discussionsupporting
confidence: 56%
“…Another study measured maternal and fetal penicillin G levels after one intramuscular dose of penicillin G benzathine. This study showed levels above the MIC at 30 days after injection 16. Our current investigation documents penicillin G levels in the fetus using the current intravascular CDC dosing regimen.…”
Section: Discussionsupporting
confidence: 56%
“…Lewin and Amstey 64 reported that treatment of colonized women and their hus- bands with benzathine penicillin/procaine penicillin injection in the third trimester was effective in reducing the colonization rate at delivery. Weeks et al 65 have recently reported a 72% reduction in GBS colonization rate and eradication of heavy GBS colonization at delivery after administration of benzathine penicillin G to women with GBS colonization at various times between 16 and 37 weeks gestation, but follow-up was unavailable for nearly a third of their subjects and no control group was studied. Now, it is generally accepted that it is extremely difficult or impossible to eradicate GBS from mucosal surfaces, 66 especially from the lower intestinal tract, 67 and that vaginal recolonization after a course of antibiotic therapy is exceedingly common, as initially reported by Hall et al 61 No studies have demonstrated an effect on neonatal infections.…”
Section: Antepartum Prophylaxismentioning
confidence: 99%
“…74 Amniotic fluid concentrations were comparable to maternal serum levels 78 and were considered sufficient to inhibit penicillin-sensitive bacteria. 72, 73, 75, 78 Based on renal elimination rates of penicillin in the 3 rd trimester, a four-hour dosing interval is considered optimal to achieve adequate amniotic fluid levels that will inhibit penicillin-sensitive bacteria. 72 …”
Section: Resultsmentioning
confidence: 99%